Americas political system - Woll, P., Binstock, R. H. (New York McGraw-Hill, Inc., 1991)
Its a comprehensive mainstream introduction to the whole landscape of American government. An examination of our rich constitutional and political traditions is complemented by an analysis of contemporary political institutions and practices. American politics is examined within the context of the Constitution, giving students yje background to campare American democracy today with the Founding Fathers intensions and hopes for a balanced, representative, and effective national government.
Keywords: Politics